2014
DOI: 10.4291/wjgp.v5.i1.48
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic colitis: Common cause of unexplained nonbloody diarrhea

Abstract: Microscopic colitis (MC) is characterized by chronic, watery, secretory diarrhea, with a normal or near normal gross appearance of the colonic mucosa. Biopsy is diagnostic and usually reveals either lymphocytic colitis or collagenous colitis. The symptoms of collagenous colitis appear most commonly in the sixth decade. Patients report watery, nonbloody diarrhea of a chronic, intermittent or chronic recurrent course. With collagenous colitis, the major microscopic characteristic is a thickened collagen layer be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 42 publications
0
47
0
5
Order By: Relevance
“…Poisson's regression analysis demonstrated that the incidence of MC increased over time, and the incidence of MC by the end of 2001 was 19.6 per 100,000 [5]. The incidence of MC increases substantially with advancing age [11]; LC affects similar numbers of men and women, while CC is up to 20 times more frequent in women than in men [9,12].…”
Section: Epidemiologymentioning
confidence: 97%
See 3 more Smart Citations
“…Poisson's regression analysis demonstrated that the incidence of MC increased over time, and the incidence of MC by the end of 2001 was 19.6 per 100,000 [5]. The incidence of MC increases substantially with advancing age [11]; LC affects similar numbers of men and women, while CC is up to 20 times more frequent in women than in men [9,12].…”
Section: Epidemiologymentioning
confidence: 97%
“…Epidemiological studies have shown that the actual incidence and prevalence of MC are higher than initially thought and still show a rising incidence, although this rise is far less pronounced than in the past [9]. A populationbased cohort study conducted from 1985 to 2001 in Olmsted County, Minnesota, showed that the incidence of CC was 3.1 per 100,000 and that of LC was 5.5 per 100,000 [5,10].…”
Section: Epidemiologymentioning
confidence: 98%
See 2 more Smart Citations
“…2) [4,62,63]. Для исключения глютенчувствитель-ной целиакии целесообразно проведение серологического ана-лиза (антиэндомизиальные антитела, антиглиадиновые антите-ла, антиретикулиновые антитела) и гистологического исследова-ния биоптатов двенадцатиперстной и тощей кишки [64].…”
Section: терапевтический архив 4 2015unclassified